Acceptability and attributes of the COVID-19 vaccine: an application of the diffusion of innovation theory in the Philippines - Engracia Arceo; Genevieve Dizon; Michael Dizon; Nestor Sibug; James Ryan Mendoza; Raphael Enrique Tiongco (International Journal of Public Health Science (IJPHS), 2022)
With the Philippines’ experience on vaccine hesitancy, the study aimed to determine the acceptability of COVID-19 vaccination in the country and understand its attributes using the Diffusion of Innovation (DoI) Theory.  The cross-sectional study included 327 respondents recruited for four weeks through various social media platforms. Participants were requested to answer a self-administered online questionnaire. Majority of the respondents belong to age group 21-30 (46.2%), mostly female (65.4%), relatively healthy (86.2%), college graduate (37.6%), and currently unemployed (50.8%). While the majority have the intention to get vaccinated against COVID-19 (70.0%), only 16.8% are innovators belonging to the age group 21-30 (p value = 0.03), male (p value <0.001), and employed (p value= 0.01). Relative advantage (p value <0.001), compatibility (p value <0.001), observability (p value <0.001), and perceived risk (p value <0.001) are significantly associated with the intention for COVID-19 vaccination and adopter category. Findings prove that the attributes of DoI are predictors for the acceptability and timing of COVID-19 vaccination. Strategies that promote trust, information transparency, and better information dissemination on the benefits and safety of vaccination can motivate more Filipinos to adopt the innovation.